Correlation between computer tomography‐derived scar topography and critical ablation sites in postinfarction ventricular tachycardia. (5th March 2018) - Ghannam, Michael; Cochet, Hubert; Jais, Pierre; Sermesant, Maxime; Patel, Smita; Siontis, Konstantinos C.; Morady, Fred; Bogun, Frank
Abstract: Background: Myocardial wall thickness (WT) in patients with a prior myocardial infarction has been used to indicate scarring. However, the correlation of WT with sites critical to ventricular tachycardia (VT) has not been previously investigated. The purpose of this study was to correlate electroanatomic mapping data obtained during VT ablation with WT determined by cardiac computed tomography (CT). Methods and results: Cardiac CTs were performed in 15 consecutive patients (mean age 63 ± 10 years, 86% male, left ventricular ejection fraction 27 ± 12%) with a prior infarct referred for VT ablation. The CTs were registered to the electroanatomic maps obtained during the mapping procedure. Pacing was performed throughout the scar at sites with fractionated electrograms and isolated potentials. Ablation sites were identified by pace‐mapping or entrainment‐mapping and these sites were correlated with WT. Bipolar and unipolar voltage amplitude and bipolar electrogram width correlated with WT (correlation coefficient: 0.63, 0.65, and 0.41, respectively, P < 0.001). Ablation target sites were identified for 58 of 113 inducible VTs. The ablation target sites were located on CT‐defined ridges (WT: 4.2 ± 1.2 mm) bordered by areas of thinning (WT: 2.6 ± 1.1 mm, P < 0.0001) in 14 of 15 patients. Ablation targets were found on ridges in 49 of 58 VTs (84%) for which target sites were identified. A total of 70 ridges were localized in the 15 patients. VT became noninducible postablation in 11 of 15 patients (73%). Conclusion: WT measured by CT identifies ridges of myocardial tissue that often are critical for postinfarction VT and that can be appropriate target sites for ablation.